An Exploration of Factors That Motivate Human Rights Workers Working in Areas With Armed Conflict in the Philippines - Hernandez, John Francis (Archīum Ateneo, 2020)
This study examined the experiences and motivation of human rights workers (HRWs) in areas affected by armed conflict in the Philippines. Six human rights workers from Karapatan responded to semi-structured interviews. Karapatan is a Philippine NGO whose mission is to uphold human rights and document instances of human rights violations. The results described the risks experienced by human rights workers in conflict afflicted areas in the country. Intrinsic factors that motivate HRWs to continuously engage in human rights work despite facing adverse situations include altruism; belief that they are advocating a just cause; feeling a sense of fulfillment; and strongly identifying with their work. Findings likewise show that human rights workers draw strength from the relationships that they have with their partner communities. They are motivated to match the courage of community members (tumbasan ang tapang); and are strengthened by the strong and reciprocal bonds that they have with the communities that they serve. Implications on selecting; preparing; developing and providing organizational support to human rights workers are discussed.